Charasteristics of Ageing Population in Semarang City - Puji Hardati (Universitas Muhammadiyah Surakarta, 2005)
Increase of amount of ageing population represent the indication that a region have experienced of the ageing population. In some developing countries, of including Indonesia, growth of ageing population are estimate will mount quickly in period to come, although its percentage do not same. Whereas characteristic do not know surely. This matter is caused by there is view that ageing population of still not yet of this problem, but within long term will be are problem of if are not paid attention since now. Studying of ageing population of pursuant to its characteristic will assist in handling good problems now and also to come. With the existence of data of usable ageing population resident characteristic for the materials of population development planning in area.